PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT.SECURINDO PATCKATAMA INDONESIA CABANG PEKANBARU - Irawan, Dika (Jurnal Ekonomi Bisnis Kompetif, 2023)
This research aims to find out whether there is an influence of Leadership and Work Discipline at PT. Securindo Patchatama Pekanbaru Branch, and the sample was selected using the census method by taking all the existing population. The sample obtained was 38 respondents. The respondents were employees at PT. Securindo Patchatama Pekanbaru Branch. Data processing and analysis uses multiple linear regression analysis using the SPSS 23 program. The results of this research prove that partially Leadership (X1) and Work Discipline (X2) have a significant effect on Employee Performance (Y). Meanwhile, simultaneously it also shows that Leadership (X1) and Work Discipline (X2) have a significant effect on Employee Performance with a significant value of 0.000 < 0.05 and Fcount > Ftable, namely 16.226 > 3.024. The Adjusted R Square value shows a result of 0.895, which means that 89.5% of employee performance is influenced by leadership (X1) and work discipline (X2). Meanwhile, the remaining 10.5% is influenced by other variables outside this research.